Pengaruh Model Pembelajaran Talking Stick Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas Vlll SMP Negeri 3 Lintongnihuta Tahun Pembelajaran 2023/2024. - Tio Kartika Sembiring; Eben H. Telaumbanua; Andar Gunawan Pasaribu; Raikhapoor Raikhapoor; Andrianus Nababan (Pusat Riset dan Inovasi Nasional, 2023)
The research aims to determine the positive and significant influence of the talking stick learning model on the active learning of PAK class VIII students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the talking stick learning model on the active learning of PAK students in class VIII of SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year. This research is a regression research using Descriptive Statistics techniques. The population of all class VIII students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year who are Protestant Christians is 177 people. Random sampling (random sampling) is 30% of the total population, namely 55 people. The research instrument is a closed questionnaire. The results of the analysis requirements obtained the value rxy=0.554>rtabel=0.226 and tcount=4.845>ttable=2.000 showing that there is a relationship between the talking stick learning model and the learning activeness of PAK class VIII students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year and obtained the regression equation. Hypothesis testing obtained Fcount=23.502>Ftable=1.39 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence of the talking stick learning model on the learning activeness of PAK class VIII students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year, amounting to 30.69%.